Arabica Coffee Arthropod Pests and Their Management in Ethiopia: Current Status and Future Prospective - Tamiru Shimales; Desalegn Alemayehu (Tunisian Journal of Plant Protection, 2024)
Shimales, T., and Alemayehu D. 2024. Arabica coffee arthropod pests and their management: Current status and future prospective. Tunisian Journal of Plant Protection 19 (2): 69-85.